If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2m+3)(3m+2)=0
We multiply parentheses ..
(+6m^2+4m+9m+6)=0
We get rid of parentheses
6m^2+4m+9m+6=0
We add all the numbers together, and all the variables
6m^2+13m+6=0
a = 6; b = 13; c = +6;
Δ = b2-4ac
Δ = 132-4·6·6
Δ = 25
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{25}=5$$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(13)-5}{2*6}=\frac{-18}{12} =-1+1/2 $$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(13)+5}{2*6}=\frac{-8}{12} =-2/3 $
| -3x+4(5x-11)=-180 | | 9x/5=59 | | n-2/n=4/2 | | 8(10x+3)=3-(x-7) | | 3x-4+1/4=5x/2+2 | | 9x÷5=59 | | 9x÷5=9 | | a6=50 | | 120=8(x+8)-8 | | -5b-1=-10-3b-5b | | -3x-27=9 | | 9x+10=8x+7 | | 8/4=5/a | | 121-y=206 | | (M-15)/6-(5m-4)/7=3 | | 185=2-y | | n+14=-5=9 | | X+12+3x=2(6+2x) | | 2(t-(4t+17)+11)=2(t+6) | | 18=(2x-8) | | 12t=8t+15 | | 6x-12=2x-16 | | 6z=2z-16 | | 182928718272817q=1 | | -0.4x+3.9=5.78 | | 30-(3c+4=2(c+7)+c | | 8/3a=5/9 | | -10=h-4-6 | | -4p-3(5-4p)=6(p-3)-17 | | 4n+5n=45 | | 3,9+5,2x-1,6x=18,48 | | 15x20=5 |